Infographic: Union Cycliste Internationale (UCI) pregnancy and postpartum guidance - Heron, N.; Jones, N.; Bigard, X.; Rankin, A.; Fallon, T. (Journal of Science and Cycling, 2024)
Historically, women have participated in elite sports for the past century, yet a perception persists that elite sports are incompatible with motherhood. There is a lack of consensus and sport-specific guidance on the upper limits of exercise during these periods. Arguably, this creates a conservative ambiguity for mothers who were active before pregnancy, potentially resulting in reduced participation during pregnancy and posing challenges for their return to sport postpartum. The Union Cycliste Internationale (UCI) has taken a proactive step in ensuring that pregnancy is not perceived as a barrier to exercise and has recently published its first pregnancy and postpartum guidance. To enhance awareness and accessibility of the newly published sports-specific guidance, the UCI has developed the following infographic. It is hoped that this guidance will encourage safe participation in the sport of cycling across all levels throughout pregnancy and the postpartum period.